2012
DOI: 10.1038/ni.2454
|View full text |Cite
|
Sign up to set email alerts
|

The CD46-Jagged1 interaction is critical for human TH1 immunity

Abstract: CD46 is a complement regulator with important immune-related roles. CD46 functions as a pathogen receptor and is a potent co-stimulator for the induction of interferon-γ (IFN-γ)-secreting T helper 1 (TH1) effector T cells and their subsequent switch into interleukin-10 (IL-10)-producing regulatory T cells. Here, we identify the Notch protein family member Jagged1 as a new physiological ligand for CD46. Further, CD46 regulates Notch receptors and ligands expression during T cell activation and disturbance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
194
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 158 publications
(211 citation statements)
references
References 49 publications
9
194
1
4
Order By: Relevance
“…Disruption of immunomodulatory role of CD46 may cause susceptibility to infections or development of autoimmunity. CD46 is normally believed to engage with CD4+ T-cell receptor to induce Th1 cells and interact with extracellular ligand Jagged1 resulting in switch to interleukin-10 secreting regulatory T cells, facilitating B-cell activation [15]. T cells from a CD46-deficient patient were reported to have impaired IgG production [16], which may explain the known association between a subset of patients with homozygous CD46 deficiency and common variable immunodeficiency [6,10].…”
Section: Discussionmentioning
confidence: 97%
“…Disruption of immunomodulatory role of CD46 may cause susceptibility to infections or development of autoimmunity. CD46 is normally believed to engage with CD4+ T-cell receptor to induce Th1 cells and interact with extracellular ligand Jagged1 resulting in switch to interleukin-10 secreting regulatory T cells, facilitating B-cell activation [15]. T cells from a CD46-deficient patient were reported to have impaired IgG production [16], which may explain the known association between a subset of patients with homozygous CD46 deficiency and common variable immunodeficiency [6,10].…”
Section: Discussionmentioning
confidence: 97%
“…48 The underlying immunological dysfunction was described in one paper as a diminished T-helper 1 response. 49 Patients with Pfeiffer syndrome (#MIM 101600, FGFR1) have overlapping features with CHARGE syndrome regarding cleft-lip and/or palate and hearing loss. 39 The immunological function in 12 patients with craniofacial malformation syndromes, including Pfeiffer syndrome, was studied by Scheuerle et al 50 Unfortunately, they did not specify the immunological dysfunction per syndrome.…”
Section: Immunological Abnormalities Reported In Charge Syndromementioning
confidence: 99%
“…The generation of C3a and C3b by human CD4 + T cells (8) is essential for the development of Th1 cell-mediated responses through autocrine stimulation of the C3aR and the complement membrane regulator CD46, respectively (9,10). To further define the mechanism governing C3a and C3b generation by CD4 + T cells, Liszewski et al (4) demonstrated that activation occurs inside the CD4 + T cell and that the processing into C3a and C3b is convertase independent, but cathepsin L (CTSL) dependent.…”
Section: Introductionmentioning
confidence: 99%